2013
DOI: 10.1002/ccd.24591
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after primary percutaneous coronary intervention in octogenarians and nonagenarians with ST‐segment elevation myocardial infarction: From the Western Denmark heart registry

Abstract: The annual proportion of octogenarians with STEMI treated with PPCI doubled from 2002 to 2009, while the proportion of nonagenarians remained unchanged. Although nonagenarians had the highest short- and long-term mortality, we found the outcome acceptable with a 5-year survival of more than 40% in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 35 publications
12
52
2
Order By: Relevance
“…In-hospital mortality was low (19%), but was significantly higher in patients with shock. A recent Danish study that included 109 nonagenarians undergoing PCI after STEMI showed a 30-day mortality of 25.8%, a 1-year mortality of 32.5%, and a 5-year mortality of 57.3% [26]. Those three small registries suggested that selected nonagenarians with STEMI benefit from pPCI.…”
Section: Discussionmentioning
confidence: 97%
“…In-hospital mortality was low (19%), but was significantly higher in patients with shock. A recent Danish study that included 109 nonagenarians undergoing PCI after STEMI showed a 30-day mortality of 25.8%, a 1-year mortality of 32.5%, and a 5-year mortality of 57.3% [26]. Those three small registries suggested that selected nonagenarians with STEMI benefit from pPCI.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the Western Denmark Heart Registry analysis of primary PCI in octogenarians and nonagenarians with STEMI showed that a total of 1,322 elderly patients were treated with primary PCI, which corresponds to 11.6% of the total STEMI population treated with primary PCI 9. In another study, performed in Turkey, Oduncu et al10 reported that 8.1% of the primary PCI population consisted of patients aged ≥80 years.…”
Section: Current Status Of Primary Pci In the Elderly With Stemimentioning
confidence: 99%
“…PCI is being increasingly performed in elderly patients [8,9,10,11]. Reported peri-procedural mortality is 6.9-7.6% in elective procedures [9,12,13,14], but can be as high as 15.5-17.2% in octogenarians with acute ST elevated myocardial infarcts [15,16]. Patients' subjective perception of their HRQOL is equally as important as objective end-points such as mortality in considering PCI [4,17,18].…”
Section: Introductionmentioning
confidence: 99%